An empirical survey of certain key aspects of the use of statistical sampling by South African registered auditors accredited by the Johannesburg securities exchange - Swanepoel, Elmarie (Stellenbosch : Stellenbosch University, 2011)
Thesis (MAcc)--Stellenbosch University, 2011.